Likelihood Ratio Tests in Linear Models with Linear Inequality Restrictions on Regression Coefficients - Miguel Fonseca; João Tiago Mexia; Bimal K. Sinha; Roman Zmyślony (Revstat Statistical Journal, 2015)
This paper develops statistical inference in linear models, dealing with the theory of maximum likelihood estimates and likelihood ratio tests under some linear inequality restrictions on the regression coefficients. The results are widely applicable to models used in environmental risk analysis and econometrics.